The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s1516-44462004000400006
|View full text |Cite
|
Sign up to set email alerts
|

Disposição e alternativas ao dirigir alcoolizado entre jovens paulistanos

Abstract: Findings suggest that prevention efforts presenting a spectrum of alternatives to drunk driving and the enforcement of drink and driving laws would be two useful addenda to the more severe laws created in the 1998 Traffic Code.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
0
3
0
9
Order By: Relevance
“…Similarly, young people have a higher prevalence of driving after drinking alcohol and being a passenger of a driver who drank alcohol. 8 In Brazil, a study identified the risk profile for drinking and driving in 2,166 youths. 9 The characteristics associated with drinking and driving were high alcohol intake, being a frequent passenger of a driver who drank and drove, having friends who drink and drive, and considering high alcohol intake to be safe for driving.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, young people have a higher prevalence of driving after drinking alcohol and being a passenger of a driver who drank alcohol. 8 In Brazil, a study identified the risk profile for drinking and driving in 2,166 youths. 9 The characteristics associated with drinking and driving were high alcohol intake, being a frequent passenger of a driver who drank and drove, having friends who drink and drive, and considering high alcohol intake to be safe for driving.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 In addition to being a key indicator of alcohol abuse, it also indicates the frequency and circumstances of alcohol consumption and the proportion of people who drink to intoxication in a specific location, region, or country. 4 The literature shows that binge drinking is a defining factor of high-risk behavior both for drivers and for other road users 3,7 and is linked to reckless driving 8 and violation of other traffic laws. 9 The blood alcohol concentration (BAC) limit for drivers in Brazil has been zero since 2008, and violation (any level of alcohol content) is punishable by fine, suspension or revocation of license, and driver detention.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,6 O índice de acidentes relacionados ao uso de anfetaminas encontrado na presente pesquisa (27%) foi maior que o relacionado ao consumo de álcool (17%). Isso sugere a necessidade de discutir esse problema nos meios de comunicação para uma campanha mais informativa sobre os riscos de ingestão dessas substâncias no período de trabalho.…”
Section: Discussionunclassified
“…A bebida alcoólica também é muito consumida entre os caminhoneiros, além de ser uma das principais causadoras de acidentes e mortes no trânsito. 2,3,6 Associado a fatores socioeconômicos, como dívidas pessoais, crise no setor de transportes e exigências de entrega de cargas em curto prazo, muitos caminhoneiros chegam a rodar mais de 18 horas por dia para cumprir horários. Eles recorrem ao uso de anfetaminas e álcool para reduzir o sono e aliviar a ansiedade, respectivamente.…”
unclassified
“…Estes dados se relacionam, provavelmente, às campanhas de prevenção de acidentes de trânsito, demonstrando que é possível educar e estimular os jovens motoristas a adotarem atitudes saudáveis e de impacto social positivo (13) .…”
Section: Resultsunclassified